2007
DOI: 10.1016/j.mrfmmm.2006.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the genetic effects of equimolar doses of ENU and MNU: While the chemicals differ dramatically in their mutagenicity in stem-cell spermatogonia, both elicit very high mutation rates in differentiating spermatogonia

Abstract: Mutagenic, reproductive, and toxicity effects of two closely related chemicals, ethylnitrosourea (ENU) and methylnitrosourea (MNU), were compared at equimolar and near-equimolar doses in the mouse specific-locus test in a screen of all stages of spermatogenesis and spermiogenesis. In stemcell spermatogonia (SG), ENU is more than an order of magnitude more mutagenic than MNU. During post-SG stages, both chemicals exhibit high peaks in mutation yield when differentiating spermatogonia (DG) and preleptotene sperm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 42 publications
4
8
0
1
Order By: Relevance
“…These observations together with the high penetrance of phenotypes that was resolved by the fourth generation of non-transgenic offspring points to an epigenetic mechanism driving impaired development. It is unlikely that hKDM1A expression during spermatogenesis behaves comparable to a chemical mutagen or induces a mutator phenotype in germ cells or offspring given the very high frequency of abnormalities observed (44)(45)(46). Consistent with that notion, our assessments using multiple approaches revealed no DNA damage or chromatin instability.…”
Section: Discussionsupporting
confidence: 82%
“…These observations together with the high penetrance of phenotypes that was resolved by the fourth generation of non-transgenic offspring points to an epigenetic mechanism driving impaired development. It is unlikely that hKDM1A expression during spermatogenesis behaves comparable to a chemical mutagen or induces a mutator phenotype in germ cells or offspring given the very high frequency of abnormalities observed (44)(45)(46). Consistent with that notion, our assessments using multiple approaches revealed no DNA damage or chromatin instability.…”
Section: Discussionsupporting
confidence: 82%
“…This was not detected in other cell types, namely spermatocytes or spermatids; mRNA expression of bcl‐2 was also decreased in spermatogonia more than in spermatocytes and spermatids when treated with the lowest concentration of ENU. This result confirms that of a previous study in vivo , in which differentiating spermatogonial cells were observed to be the most sensitive testicular cells to ENU damage, due to their higher mitotic rate compared to other spermatogenic cells [Russell et al, ]. The data presented here show that the expression level of p53 is high in spermatogonial cells compared to levels in spermatocytes and spermatids; a potential consequence of actively dividing spermatogonia which are the most susceptible male germ cell.…”
Section: Discussionsupporting
confidence: 92%
“…Mutant frequencies in male rat germ cells were determined after exposure to ENU, MNU, 6MP, 5BrdU, MMS, and EMS and thus have been reported to cause specific DNA damage in isolated germ cells from adult rat testis [Ehling et al, ; Anderson et al, ; Russell et al, ; Levkoff et al, ; Kanemitsu et al, ; Habas et al, ]. To examine species differences in the DNA damage between rats and mice three male germ cell mutagens (ENU, 6‐MP and MMS) were selected for testing.…”
Section: Discussionmentioning
confidence: 99%
“…That there is indeed a low frequency of spontaneous mutations in mammalian germline cells was suggested by early studies of mice [2,3]. The specific locus test was used to examine spontaneous and induced germline mutation frequencies to evaluate the effects of suspected genotoxins [4][5][6][7][8]. These and related studies estimated the spontaneous mutation frequencies for female and male germ cells to be approximately 1.4 3 10 À6 and 6.6 3 10 À6 , respectively [9].…”
Section: Introductionmentioning
confidence: 99%